Social media chat data visualization - Tan, Royce Chun Wei (Nanyang Technological University, 2023)
There are various existing applications that analyzes the chat log for instant messaging applications such as WhatsApp and Telegram. The primary goal of this project is to aid in a quick understanding of a long chat history. This project makes use of Term Frequency-Inverse Document Frequency (TF-IDF), an algorithm for Natural Language Processing, to identify important words or possibly topics being discussed every week throughout the chat history. This project also features other functions to display who sent the longest messages, generate a word cloud, frequency of words, and the most popular emoji within the group or a one-to-one chat log. The author also explored using various parameters to create a sensible output.